PENERAPAN GOOD GOVERNANCE DALAM PENETAPAN APBD - Parapat, Natalia; Yuliani, Febri; Tinov, M.Y. Tiyas (Jurnal Ilmu Administrasi Negara, 2018)
The Implementation of Good Governance in the Determination of APBD. This study aims to determine and analyze how the implementation of goodgovernance in the determination of APBD in the City of Padangsidimpuan. The type of research is qualitative. The research informants are the local government budget team, the DPRD budget body, and the Kota Padangsidimpuan community. Data collection methods were conducted with in-depth interviews with informants and documentation studies. The method of data analysis using qualitative descriptive approach. The results showed that the implementation of goodgovernanced in determination of APBD Kota Padangsidimpuan 2016 has been implemented by the executive and the legislative Padangsidimpuan although not yet running maximally because there is still differences in perception between the government with the community to some point in principle good Such governance as the principle of community participation, rule of law, transparency, responsiveness, consensus orientation and effective and efficient. This is due to the declining revenue of Padangsidimpuan in 2016, where local revenue conditions from relatively few sources have not reached the target.